2022
DOI: 10.3389/fpsyg.2022.892278
|View full text |Cite
|
Sign up to set email alerts
|

E-Portfolio as an Evaluative Tool for Emergency Virtual Education: Analysis of the Case of the University Andres Bello (Chile) During the COVID-19 Pandemic

Abstract: The pandemic had serious implications for university education, specifically due to the transition from face-to-face teaching to online methodologies. This article analyzes the perception of students undergoing speech therapy from a Chilean University about the E-portfolio incorporation as an evaluative tool during the emergency virtual teaching due to the COVID-19 pandemic. From quantitative research, a survey of 38 questions based on Likert scales was applied to 108 penultimate year undergraduate students. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…For student-student collaboration, three main types were identified: peer evaluation (including peer review and feedback), cooperative e-portfolio making, and peer assistance through social interaction. Rodriguez et al (2022) emphasised the significance of student-student collaboration, especially for implementing the new evaluation system, the e-portfolio-based assessment. They included co-evaluation, allowing students to reflect on and incorporate the ideas of their classmates responsible for constructing the projects.…”
Section: Bibliometric Information and Main Themes Of The Chosen Papersmentioning
confidence: 99%
See 3 more Smart Citations
“…For student-student collaboration, three main types were identified: peer evaluation (including peer review and feedback), cooperative e-portfolio making, and peer assistance through social interaction. Rodriguez et al (2022) emphasised the significance of student-student collaboration, especially for implementing the new evaluation system, the e-portfolio-based assessment. They included co-evaluation, allowing students to reflect on and incorporate the ideas of their classmates responsible for constructing the projects.…”
Section: Bibliometric Information and Main Themes Of The Chosen Papersmentioning
confidence: 99%
“…It was revealed that pupils appreciated peer input substantially. Rodriguez et al (2022) advocated the collaborative development of knowledge through exchanging resources and reflections among peers as another layer of student-student cooperation. Likewise, in the study conducted by Abuzaid et al (2021), students valued their engagement with peers since they were able to communicate their opinions and get feedback; interaction with classmates increases student learning and productivity.…”
Section: Bibliometric Information and Main Themes Of The Chosen Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…
With the onset of the COVID-19 pandemic, technological transformation in higher education was promoted globally. While e-portfolios are not necessarily new as an educational approach, their significance as an alternative online assessment model increased during this rapid, compulsory shift from face-to-face learning into distance learning modes (Rodriguez et al, 2022). Meanwhile, amidst the unprecedented pedagogical and technological changes, mental health issues are an alarming concern.
…”
mentioning
confidence: 99%